Re-Desain Interior KORIDOR Co-working Space di Surabaya - Ellen Nadia Precilia; Hedy Constancia Indrani; Hendy Mulyono (Intra, 2018)
KORIDOR co-working space is a place made by Surabaya City Government that aims to provide education to the people of Surabaya, but because the concept and interior is less than the maximum, re-design required in the interior. The re-design of this public facility also aims to accommodate people such as freelancers, startups, and students who have no place to work, but it can also be a place for visitors to interact and socialize with others. There are several stages of the design method, which are empathize stage, define stage, ideate stage, prototype stage, and test phase. The solutions offered by the concept of unite diversity KORIDOR are applied within the modular furniture, multifunctional space, and the used of technology that supports education, the open plan principle is also applied to support the users’ communication. The result of the design is KORIDOR requires multifunctional space and modular furniture, because of the uncertain amount of users, and also their dynamic activities.